The Role of Fieldwork Practice in Developing Professional Competence of Christian Religious Education Students - Serdianus; Rando, Anugerah Agustus; Parai', Nelsi; Rumono, Bertrand Gerardo (Didache: Journal of Christian Education, 2025)
This study examines how fieldwork practice improves the professional competence of Christian Religious Education students. It evaluates the program to inform us of its next semester's development. Using a qualitative descriptive method, the study collected data through interviews with 11 mentor teachers and 52 randomly selected students of fieldwork practice. The data was analyzed using Atlas.ti, following the steps outlined by Miles and Huberman. The findings reveal that the students demonstrate teaching planning, implementation, and evaluation skills. They are also proficient in integrating technology and instructional media. Overall, the students effectively fulfilled their responsibilities and performed their roles and functions in the learning process well. They demonstrated satisfactory professional competence, including understanding and explaining course materials, classroom management, communication, feedback reception, ethics, and integrity. With some of the challenges of fieldwork practice, the faculty must improve the program preparations and implementation quality.